Mitral subannular left ventricular aneurysm. A case presenting with ventricular tachycardia. - Fitchett, D H (1983)
A young African immigrant presented with ventricular tachycardia in association with two mitral subannular left ventricular aneurysms. Although an unusual finding, the recognition of such aneurysms is important as prophylactic measures may prevent complications. Furthermore, they are a surgically treatable cause of heart failure and arrhythmias.